From P(t,s) = exp {−∫_{0}^{s−t }f(t,x)dx}, we get

d_{t }logP(t,s) = f(t,x) dt − ∫_{0}^{x}dy dt f(t,y) —– (1)

_{t}F(f) = ∂F/df dtf + 1/2 ∫ dx ∫ dx′ ∂^{2}F/∂f(t,x)∂f(t,x′) Cov [d_{t}f(t,x), d_{t}f(t,x′)] —– (2)

Skip to content
# AltExploit

## Schoolboy Errors: Rhizomatic Dysphoria ∃! Machinic Kernel Panic: The Maximalist Politic of Self

# No-Arbitrage & Conditional Drift from the Covariance of Fluctuations. (Didactic 4)

From P(t,s) = exp {−∫_{0}^{s−t }f(t,x)dx}, we get

d_{t }logP(t,s) = f(t,x) dt − ∫_{0}^{x}dy dt f(t,y) —– (1)

_{t}F(f) = ∂F/df dtf + 1/2 ∫ dx ∫ dx′ ∂^{2}F/∂f(t,x)∂f(t,x′) Cov [d_{t}f(t,x), d_{t}f(t,x′)] —– (2)

%d bloggers like this: